MASKULINTAS DALAM TERJEMAHAN BABAD SUMENEP KARYA H. WERDISASTRO - Fajriana, Anisa; Supratman, M. Tauhed; Kasanova, Ria (Kantor Bahasa Banten, 2017)
Literary works are beautiful works of art and are the fulfillment of human need for the instinct of beauty. Literary works can give a reasoning sense, but that knowledge can come alive in literary works. Literary works have souls because they are woven with taste. The soul in literary works is formed from the characteristic sharing of its characters. It can be seen one of them with the masculinity of a man, such as the courage in the leadership shown by Ramuk in the translation of Bumen Sumenep Karya H. Werdisastro. The utilization of this research result can theoretically be used as a learning material and reference in literary teaching, whereas the utilization can be applied in the form of identifying the characteristics of masculinity in a literary work, both literary works of general and general literature. The results of Masculinity research in Sumenep's Babad Translation of H. Werdisastro's Work concludes: a). leadership, (b) compassion, and (c) protection consisting of: courage and determination.